Adjustment for survey non-participation using record linkage and multiple imputation: A validity assessment exercise using the Health 2000 survey. Issue 2 (March 2023) - Mcminn, Megan A.; Martikainen, Pekka; Härkänen, Tommi; Tolonen, Hanna; Pitkänen, Joonas; Leyland, Alastair H.; Gray, Linsay
Aims: It is becoming increasingly possible to obtain additional information about health survey participants, though not usually non-participants, via record linkage. We aimed to assess the validity of an assumption underpinning a method developed to mitigate non-participation bias. We use a survey in Finland where it is possible to link both participants and non-participants to administrative registers. Survey-derived alcohol consumption is used as the exemplar outcome. Methods: Data on participants (85.5%) and true non-participants of the Finnish Health 2000 survey (invited survey sample N =7167 aged 30-79 years) and a contemporaneous register-based population sample ( N =496, 079) were individually linked to alcohol-related hospitalisation and death records. Applying the methodology to create synthetic observations on non-participants, we created 'inferred samples' (participants and inferred non-participants). Relative differences (RDs) between the inferred sample and the invited survey sample were estimated overall and by education. Five per cent limits were used to define acceptable RDs. Results: Average weekly consumption estimates for men were 129 g and 131 g of alcohol in inferred and invited survey samples, respectively (RD –1.6%; 95% confidence interval (CI) –2.2 to –0.04%) and 35 g for women in both samples (RD –1.1%; 95% CI –2.4 to –0.8%). Estimates for men with secondary levels of education had the greatest RD (–2.4%; 95% CI –3.7 to –1.1%). Conclusions: The sufficiently small RDs between inferred and invited survey samples support the assumption validity and use of our methodology for adjusting for non-participation. However, the presence of some significant differences means caution is required.